Improving the safety of high-rise house-building based on the risk of introduction of protective actions - Верюжський, Ю.В.; Бакулін, Є.А. (Proceedings of National Aviation University (archive), 2007)
The analysis of various factors action that of probable threats of high-altitude buildings of mass construction influencing safety is lead. The estimation of a buildings safety from a position of their reliability and security from risks is given.